Effectiveness of the compound chlorpyrifos plus cypermethrin plus citronellal against Alphitobius diaperinus. Laboratory analysis and residue determination in carcasses - Silva, G. S.; Michels, M. G.; Toma, S. B.; Terra, F. E.; Soares, V. E. [UNESP]; Costa, A. J. [UNESP] (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2007)
Biological security and the absence of residues in meat Effectiveness, and/or eggs must be considered when recommending options for the control Alphitobius diaperinus in poultry production environments. This research study evaluated the effectiveness of cypermethrin+chlorpyrifos+citronellal in the control of A. diaperinus, including analysis for the presence of residues of this compound in poultry carcasses (experimental farm). Two studies were carried out under laboratory conditions. One used paper filters a four dilutions of the compound, and the other used a container including with pulverized broiler litter and the compound. The analysis of carcasses for residues was conducted in broilers that raised in a broiler house treated (floor and/or litter) with the compound at a dilution of 1:800. Birds were regularly sacrificed, submitted to necropsy, and liver, muscle and fat fragments were collected. Gas chromatography was used to identify the possible presence of any chemical residue in these samples. High effectiveness rates against A.diaperinus were observed in the two laboratory studies, as well as the absence of residues in the carcasses. This compound, can be recommended as a valuable used in the studied concentrations, alternative for the control and treatment of A. diaperinus.
Keywords: Alphitobius diaperinus; Broiler; Cypermethrin plus chlorpyrifos plus citronellal; Residue